Data communication linking NAO robot and IoRT network in autism's Tele-rehabilitation therapy / Muhammad Aliff Rosly … [et al.] - Rosly, Muhammad Aliff; Kamaruzaman, Dayana; Shamsuddin, Syamimi; Yussof, Hanafiah (Division of Research and Industry Linkages, 2017)
Autism is a lifelong developmental disability that effects the brain's normal development o f social and communication skills. Robot-mediated intervention utilizing NAO robot via tele-rehabilitation network has been introduced as latest technology-based solution for autism therapy, This latest technology-based solution aims to eliminate the distance barrier to serve as practical solutions to the autism population. Meanwhile, the Internet of Robotics Things (loRT) has been identified as the powerful tool offers promising solutions for connectivity of intelligent robotic devices in tele-rehabilitation environment. However, the fundamental issue on transferring data between NAO robot and loRT network has remains as the main problem that prevents the tele-rehabilitation system to be realized. As technological solution for this problem, a communication concept linking NAO Robot and loRT networks such as Microsoft Azure and ThinkSpeak is proposed. The proposed concept consists o f data communication through NAO Robot NAOqi APIs, Python SDK, and loRT network architectures. It enables two-way communication between NAO robot and loRT networks, and allows NAO robot as "things” to communicate and interact with autism patient and transfer data over pervasive networks using Internet protocols. Results show that, the communication between NAO robot NAOqi and loRT network such as Microsoft Azure and Thinkspeak through Python SDK is feasible. As a conclusion, the developed concept manages to solve the two-ways communication-issue-in-robot-mediated-intervention-environment